Development readiness - Omamo, Steven Were (International Food Policy Research Institute, 2025)
Why do some systems move while others stall—even when resources, plans, and intent appear similar? This paper introduces the concept of development readiness as one way to understand and address this question. Development readiness is defined as the capacity of a system to act—at the right time, at the right scale, and with purpose—whether in response to crises or in pursuit of development goals. It emerges when kinetic capacity (the ability to move people, goods, and services) aligns with negotiation capacity (the ability to coordinate, decide, and resolve), conditioned by activation costs (tangible and intangible obstacles) and option value (flexibility to act under uncertainty). A conceptual framework based on these four operational forces is set out and illustrated with real-world examples. A structured research agenda and strategy emerges, along with implications for investment and operations. The case illustrations demonstrate that the development readiness framework applies equally at national, sectoral, and organizational levels, with wide-ranging applications—from scaling innovations, accelerating service delivery, and strengthening value chains, to deepening climate resilience and enabling coordinated action in crisis-prone and institutionally fragmented settings.